Analisis Sengketa Kepemilikan Merek Bensu (Studi pada Merek Geprek Bensu Melawan I Am Geprek Bensu) - Levira Leo Gunawan; R. Rahaditya (Syntax Corporation, 2023)
This study has the objective of examining and analyzing disputes over the ownership of the Bensu brand and legal protection efforts in the Geprek Bensu case against I Am Geprek Bensu, which in this study discusses cases of intellectual property rights in the trademark field. This research uses a normative juridical approach with secondary, primary and tertiary data. The results of this study are that: the Geprek Bensu dispute originated from business similarities between Geprek Bensu owned by Ruben Onsu and I Am Geprek Bensu owned by PT Ayam Geprek Benny Sujono where Ruben claimed Bensu was his business; the Bensu case is that there was trademark protection out of good faith and the registration system at that time adhered to first to file, which meant that the first recipient was the one who was protected; there are many similarities between the two types of brands Bensu and Ruben were judged to have plagiarized I Am Geprek Bensu, and the Supreme Court considered the case and decided that Ruben Onsu's appeal was rejected